Land and water resources management in the Caribbean - Paul, Compton L. (Land and Water Resources Network [S.l.], 2001)
Contains the proceedings of the first Annual Technical Meeting of CLAWRENET held in Barbados in October 2000. Highlights the experiences in various aspects of natural resources management in the region and proposes a planning framework for sustainable land and water use in Small Island Developing States.